Method for preparing nanocrystal nucleus type early strength agent by using in-situ growth technology and application of nanocrystal nucleus type early strength agent

Through the combination of in-situ growth technology and aminosilane modified polycarboxylic acid dispersant, the dispersion stability problem of nano C-S-H crystalline core early strength agent is solved, significantly improving the early compressive strength of concrete, and maintaining the later strength and environmental protection characteristics.

CN119822684APending Publication Date: 2025-04-15CHAOLI(JIANGSU)CONSTR MATERIALS CO LTD

Patent Information

Application Number
CN202510008014.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, the long-term dispersion stability of nano C-S-H crystalline premature strength agents is difficult to guarantee, and the 12-h intensity improvement is not obvious.

Method used

In situ growth technology is adopted to grow nano calcium oxide on the carrier, improve its dispersion ability in water, and modify the polycarboxylic acid dispersant through aminosilane, so that the nano C-S-H crystal nuclear dispersant has high dispersion and high stability.

Benefits of technology

The high dispersion and high stability of nano C-S-H crystal core dispersants are achieved, which significantly improves the early compressive strength of concrete, and does not damage the later strength of concrete, which is green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822684A_ABST
    Figure CN119822684A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a nanocrystal nucleus type early strength agent by using an in-situ growth technology and application of the nanocrystal nucleus type early strength agent, and belongs to the technical field of concrete admixtures. The method comprises the following three steps: preparing an in-situ growth calcium source, preparing a silane modified polycarboxylic acid dispersing agent and preparing a nano hydrated calcium silicate crystal nucleus early strength agent. According to the preparation method, nano calcium oxide grows on a growth carrier by utilizing high dispersity of the growth carrier in water, so that the dispersing capacity of the nano calcium oxide in water is improved, in addition, a polycarboxylic acid dispersing agent is modified by utilizing amino silane, and a firm isolating layer with Si-O-Si as a framework is formed by utilizing the fact that silane and hydroxyl on the surface of a hydrated calcium silicate crystal nucleus can be subjected to dehydration condensation; the crystal nucleus growth is inhibited. Therefore, the nano C-S-H crystal nucleus dispersing agent has high dispersity and high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete admixtures, in particular to a method and application of a nanocrystalline core-type early strength agent prepared by utilizing an in-situ growth technology. Background Art

[0002] The development of modern construction projects has put forward higher requirements on the performance of concrete. Compared with traditional cast-in-place structures, precast concrete can improve the durability, workability, economy, and energy saving of concrete. The "14th Five-Year Plan for the Development of the Construction Industry" issued by the Ministry of Housing and Urban-Rural Development clearly puts forward the requirement that the proportion of prefabricated buildings in new buildings should reach more than 30%. Increasing the strength growth rate during the production of prefabricated components can speed up mold turnover and improve production efficiency. Component factories usually use high-temperature autoclaving and adding early strength agents to increase mold turnover. High-temperature autoclaving has the defects of high energy consumption, environmental pollution, and reduced concrete durability, and is unsustainable. Accelerating the improvement of early compressive strength at room temperature in an environmentally friendly way is a promising new strategy.

[0003] Calcium silicate hydrate (CSH) gel is the main hydration product of cement, which determines the compressive strength and durability of cement. Therefore, accelerating the cement hydration process and the formation of CSH gel in the early stage of cement hydration can promote the rapid development of early compressive strength of concrete.

[0004] In recent years, the research on nanomaterials in the field of cement materials has begun to rise and has achieved some beneficial research results. Due to its nano-scale particle size, it plays an inductive role in the early stage of cement hydration, reduces the nucleation energy barrier of cement hydration products, accelerates the cement hydration process, and improves the early strength of cement materials. Various nanoparticles, such as nano-silicon dioxide, nano-aluminum oxide, and nano-calcium carbonate, have a certain degree of acceleration effect on cement hydration. Compared with these nanoparticles, nano-CSH particles have more significant advantages in early strength performance, compatibility with cementitious materials, improving concrete durability, and shortening demoulding time. It is generally believed that the smaller the particle size of the nano-CSH crystal nucleus, the more significant the early strength effect. However, according to the nucleation-growth theory of crystals, the CSH crystal nucleus will gradually grow, thereby reducing the early strength effect. The smaller the crystal nucleus, the higher the surface energy, the more unstable it is, and it is easy to agglomerate. In the prior art, some people introduced silanes and alcohol amines as crystal nucleus growth inhibitors, Tween, Span, etc. as emulsifiers, and used the inhibitor and emulsifier to form an oil-in-water form to provide nucleation sites for the nucleation of CSH, and synthesized CSH nanocrystalline core early strength agent, but the 12h strength improvement was not obvious. In addition, polycarboxylate water reducer was used as a dispersant to synthesize CSH crystal nucleus suspension by coprecipitation technology. The crystal nucleus early strength agent synthesized in this way can be compounded with concrete admixtures in any proportion, but the long-term dispersion stability of calcium silicate hydrate crystal nucleus suspension is difficult to guarantee. Therefore, it is of great significance to study an early strength agent that can solve the problem of long-term dispersion stability and has a good effect of improving the early strength of concrete products. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a method and application of a nanocrystalline core-type early strength agent prepared by in-situ growth technology; the present invention utilizes the high dispersibility of a growth carrier in water to grow nano calcium oxide on the carrier, thereby improving the dispersibility of nano calcium oxide in water, and utilizes aminosilane to modify a polycarboxylic acid dispersant, so that the nano CSH crystal core dispersant has high dispersibility and high stability.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] In one aspect, the present invention provides a method for preparing a nanocrystalline core-type early strengthening agent using an in-situ growth technique, comprising:

[0008] 1) Mixing and stirring the treated graphite, calcium source and carboxylate for a period of time, uniformly adding a certain concentration of sodium hydroxide to the mixture at 20-50° C., and washing by centrifugation with deionized water to obtain in-situ grown nano calcium hydroxide;

[0009] The graphite pretreatment method is as follows: graphite and concentrated sulfuric acid are mixed in a ratio of 1:1, ground with a grinder for 30 minutes, then removed excess sulfuric acid by centrifugal washing, and dried for later use;

[0010] The calcium source includes one or more of calcium chloride, calcium nitrate, sulfate, calcium gluconate, and calcium lactate;

[0011] The carboxylate includes one or more of sodium citrate, sodium tartar, sodium gluconate, sodium acetate, sodium oxalate, sodium lactate, sodium stearate, and sodium acrylate;

[0012] 2) calcining the in-situ grown nano calcium hydroxide at 600° C. to obtain nano calcium oxide;

[0013] 3) mixing the polycarboxylic acid dispersant, the silane modifier and deionized water for a period of time, and adding sodium hydroxide solution to adjust the pH to about 12 to obtain a silane-modified polycarboxylic acid dispersant;

[0014] The silane dispersant includes one or more of aminosilane, 3-aminopropyltriethoxysilane, bis(tert-butylamino)silane, (3-aminopropyl)dimethylmethoxysilane, 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane, 3-aminopropyltriethoxysilane, [3-(6-aminohexylamino)propyl]trimethoxysilane, and aminoethylaminoisobutylmethyldimethoxysilane.

[0015] 4) Mixing the silane-modified polycarboxylic acid dispersant, in-situ grown nano calcium oxide and deionized water, and uniformly dropping a silicon source of a certain concentration into the mixture to obtain a CSH nanocrystalline core dispersant; the silicon source includes one or both of sodium silicate nonahydrate and sodium silicate tetrahydrate.

[0016] On the other hand, the present invention also provides a nanocrystalline core-type early strengthening agent prepared by the above method.

[0017] In another aspect, the present invention further provides a use of the above nanocrystalline core-type early strength agent added to concrete as an early strength agent, wherein the addition amount is 4-10% of the mass of the concrete.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] During the preparation process, the high dispersibility of the growth carrier in water is utilized to grow nano calcium oxide on the carrier, thereby improving the dispersibility of nano calcium oxide in water. In addition, aminosilane is used to modify the polycarboxylic acid dispersant, and silane can be used to form a strong isolation layer with Si-O-Si as the skeleton through dehydration condensation with the surface hydroxyl of the calcium silicate hydrate crystal core, thereby inhibiting the growth of the crystal core. In this way, the nano CSH crystal core dispersant can have high dispersibility and high stability. The prepared crystal core dispersant does not contain components that damage the later strength of concrete and accelerate the corrosion of steel bars, and has no loss of the later strength of concrete, no corrosion of steel bars, and is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a flow chart of in-situ growth of nano calcium oxide in Example 1 of the present invention;

[0021] Figure 2 This is a morphology diagram of the nano-CSH crystal prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, they are described in detail below in conjunction with specific embodiments.

[0023] In the present invention, the materials and reagents used can be obtained from commercial sources unless otherwise specified. Among them, the polycarboxylic acid dispersant is CL-C90.

[0024] The graphite pretreatment method is as follows: graphite (particle size is 1-20 microns) and concentrated sulfuric acid are mixed in a mass ratio of 1:1, ground with a grinder for 30 minutes, then centrifuged at 10000 rpm for 30 minutes, the supernatant is removed, water is added for washing, and the precipitate obtained after washing is repeated 3 times and dried in a 60°C oven for use.

[0025] The present invention provides a method and application of a nanocrystalline core-type early strength agent prepared by in-situ growth technology, and specific embodiments are as follows.

[0026] Example 1

[0027] A method for preparing a nanocrystalline core-type early strength agent using an in-situ growth technique, the process is as follows: Figure 1 ,include:

[0028] 1) Preparation of in-situ growth calcium source: 1.5 g pretreated graphite, 3.0 g calcium nitrate, 0.3 g sodium citrate, and 55 g water were mixed in a 250 mL conical flask, stirred at 25°C for 10 min, and 12.3 g 1 mol / L NaOH solution was added dropwise to the stirred conical flask using a peristaltic pump for 30 min. The product in the conical flask was poured into a centrifuge tube and centrifuged at 16,000 rpm for 30 min, and repeated 3 times.

[0029] 2) placing the precipitate after centrifugation into a crucible and reacting it at 600° C. for 1 h in a muffle furnace to obtain in-situ grown nano-calcium oxide;

[0030] 3) Preparation of silane-modified polycarboxylic acid dispersant: 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane, polycarboxylic acid dispersant and deionized water were mixed in a ratio of 1:6:93 and added to a reactor, stirred at a speed of 100 r / min for 1 h, and a 32% mass concentration NaOH solution was added to adjust the pH to 12 to obtain a silane-modified polycarboxylic acid dispersant;

[0031] 4) Preparation of calcium silicate nanocrystalline cores: 5.1 g of in-situ grown nano calcium oxide and 213 g of silane-modified polycarboxylic acid dispersant were added to a reactor and mixed and stirred for 20 min. 18.9 g of sodium silicate nonahydrate was prepared into a 10% solution and added dropwise to the reactor while stirring for 30 min. After the addition was completed, stirring was continued for 1 h to obtain calcium silicate nanocrystalline cores. Figure 2 shown.

[0032] Example 2

[0033] A method for preparing a nanocrystalline core-type early strength agent using an in-situ growth technique comprises the following steps:

[0034] 1) Preparation of in-situ growth calcium source: 1.5g pretreated graphite, 3.0g calcium nitrate, 0.5g sodium gluconate, and 55g water were mixed in a 250mL conical flask, stirred at 25°C for 10min, and 6g 1mol / L NaOH solution was added dropwise to the stirred conical flask using a peristaltic pump for 30min. The product in the conical flask was poured into a centrifuge tube and centrifuged at 16000 for 30min, and repeated 3 times;

[0035] 2) The precipitate after centrifugation is placed in a crucible and reacted in a muffle furnace at 600° C. for 1 h to obtain in-situ grown nano-calcium oxide.

[0036] 3) Preparation of silane-modified polycarboxylic acid dispersant: [3-(6-aminohexylamino)propyl]trimethoxysilane, polycarboxylic acid dispersant and deionized water were mixed in a ratio of 2:6:93 and added to a reactor. The mixture was stirred at a speed of 100 r / min for 1 h. A 32% NaOH solution was added to adjust the pH to 12 to obtain a silane-modified polycarboxylic acid dispersant.

[0037] 4) Preparation of calcium silicate nanocrystalline cores: 5.1 g of in-situ grown nano calcium oxide and 213 g of silane-modified polycarboxylic acid dispersant were added to a reactor and mixed and stirred for 20 min. 20.8 g of sodium silicate nonahydrate was prepared into a 10% solution and added dropwise to the reactor while stirring for 30 min. After the addition was completed, stirring was continued for 1 h to obtain calcium silicate nanocrystalline cores.

[0038] Example 3

[0039] A method for preparing a nanocrystalline core-type early strength agent using an in-situ growth technique comprises:

[0040] 1) Preparation of in-situ growth calcium source: 1.5g pretreated graphite, 3.0g calcium chloride, 0.5g sodium tartrate, and 55g water were mixed in a 250mL conical flask, stirred at 25°C for 10min, and 6g 1mol / L NaOH solution was added dropwise to the stirred conical flask using a peristaltic pump for 30min. The product in the conical flask was poured into a centrifuge tube and centrifuged at 16000 for 30min, and repeated 3 times;

[0041] 2) The precipitate after centrifugation is placed in a crucible and reacted in a muffle furnace at 600° C. for 1 h to obtain in-situ grown nano-calcium oxide.

[0042] 3) Preparation of silane-modified polycarboxylic acid dispersant: 3-aminopropyltriethoxysilane, polycarboxylic acid dispersant and deionized water were mixed in a ratio of 4:6:90 and added to a reactor, stirred at a speed of 100 r / min for 1 h, and 32% NaOH solution was added to adjust the pH to 12 to obtain a silane-modified polycarboxylic acid dispersant.

[0043] 4) Preparation of calcium silicate nanocrystalline cores: 5.1 g of in-situ grown nano calcium oxide and 213 g of silane-modified polycarboxylic acid dispersant were added to a reactor and mixed and stirred for 20 min. 15 g of sodium silicate nonahydrate was prepared into a 10% solution and added dropwise to the reactor while stirring for 30 min. After the addition was completed, stirring was continued for 1 h to obtain calcium silicate nanocrystalline cores.

[0044] Example 4

[0045] A method for preparing a nanocrystalline core-type early strength agent using an in-situ growth technique comprises:

[0046] 1) Preparation of in-situ growth calcium source: 1.5 g pretreated graphite, 3.0 g calcium nitrate, 0.5 g sodium lactate, and 55 g water were mixed in a 250 mL conical flask, stirred at 25°C for 10 min, and 6 g 1 mol / L NaOH solution was added dropwise to the stirred conical flask using a peristaltic pump for 30 min. The product in the conical flask was poured into a centrifuge tube and centrifuged at 16,000 speed for 30 min, and repeated 3 times.

[0047] 2) The precipitate after centrifugation is placed in a crucible and reacted in a muffle furnace at 600° C. for 1 h to obtain in-situ grown nano-calcium oxide.

[0048] 3) Preparation of silane-modified polycarboxylic acid dispersant: aminoethylaminoisobutylmethyldimethoxysilane, polycarboxylic acid dispersant and deionized water were mixed in a ratio of 4:6:90 and added into a reactor, stirred at a speed of 100 r / min for 1 h, and 32% NaOH solution was added to adjust the pH to 12 to obtain a silane-modified polycarboxylic acid dispersant.

[0049] 4) Preparation of calcium silicate nanocrystalline cores: 5.1 g of in-situ grown nano calcium oxide and 213 g of silane-modified polycarboxylic acid dispersant were added to a reactor and mixed and stirred for 20 min. 8.68 g of sodium silicate tetrahydrate was prepared into a 10% solution and added dropwise to the reactor while stirring for 30 min. After the addition was completed, stirring was continued for 1 h to obtain calcium silicate nanocrystalline cores.

[0050] Example 5

[0051] A method for preparing a nanocrystalline core-type early strength agent using an in-situ growth technique comprises:

[0052] 1) Preparation of in-situ growth calcium source: 1.5g pretreated graphite, 3.0g calcium nitrate, 0.7g sodium tartrate, and 55g water were mixed in a 250mL conical flask, stirred at 25°C for 10min, and 6g 1mol / L NaOH solution was added dropwise to the stirred conical flask using a peristaltic pump for 30min. The product in the conical flask was poured into a centrifuge tube and centrifuged at 16000 for 30min, and repeated 3 times;

[0053] 2) The precipitate after centrifugation is placed in a crucible and reacted in a muffle furnace at 600° C. for 1 h to obtain in-situ grown nano-calcium oxide.

[0054] 3) Preparation of silane-modified polycarboxylic acid dispersant: 3-aminopropyltriethoxysilane, polycarboxylic acid dispersant and deionized water were mixed in a ratio of 2:6:92 and added into a reactor, stirred at a speed of 100 r / min for 1 h, and 32% NaOH solution was added to adjust the pH to 12 to obtain a silane-modified polycarboxylic acid dispersant.

[0055] 4) Preparation of calcium silicate nanocrystalline cores: 5.1 g of in-situ grown nano calcium oxide and 213 g of silane-modified polycarboxylic acid dispersant were added to a reactor and mixed and stirred for 20 min. 28 g of sodium silicate nonahydrate was prepared into a 10% solution and added dropwise to the reactor while stirring for 30 min. After the addition was completed, stirring was continued for 1 h to obtain calcium silicate nanocrystalline cores.

[0056] Example 6

[0057] A method for preparing a nanocrystalline core-type early strength agent using an in-situ growth technique comprises:

[0058] 1) Preparation of in-situ growth calcium source: 1.5g pretreated graphite, 3.0g calcium nitrate, 0.2g sodium citrate, and 55g water were mixed in a 250mL conical flask, stirred at 25°C for 10min, and 6g 1mol / L NaOH solution was added dropwise to the stirred conical flask using a peristaltic pump for 30min. The product in the conical flask was poured into a centrifuge tube and centrifuged at 16000 for 30min, and repeated 3 times;

[0059] 2) The precipitate after centrifugation is placed in a crucible and reacted in a muffle furnace at 600° C. for 1 h to obtain in-situ grown nano-calcium oxide.

[0060] 3) Preparation of silane-modified polycarboxylic acid dispersant: aminoethylaminoisobutylmethyldimethoxysilane, polycarboxylic acid dispersant and deionized water were mixed in a ratio of 6:6:88 and added into a reactor, stirred at a speed of 100 r / min for 1 h, and 32% NaOH solution was added to adjust the pH to 12 to obtain a silane-modified polycarboxylic acid dispersant.

[0061] 4) Preparation of calcium silicate nanocrystalline cores: 5.1 g of in-situ grown nano calcium oxide and 213 g of silane-modified polycarboxylic acid dispersant were added to a reactor and mixed and stirred for 20 min. 28 g of sodium silicate nonahydrate was prepared into a 10% solution and added dropwise to the reactor while stirring for 30 min. After the addition was completed, stirring was continued for 1 h to obtain calcium silicate nanocrystalline cores.

[0062] To further illustrate the beneficial effects of the present invention, a comparative example is constructed as follows.

[0063] Comparative Example 1

[0064] A method for preparing a calcium silicate crystal nucleus early strength agent comprises:

[0065] 1) Preparation of in-situ growth calcium source: 1.5 g pretreated graphite, 3.0 g calcium nitrate, and 55 g water were mixed in a 250 mL conical flask, stirred at 25°C for 10 min, and 6 g 1 mol / L NaOH solution was added dropwise to the stirred conical flask using a peristaltic pump for 30 min. The product in the conical flask was poured into a centrifuge tube and centrifuged at 16,000 rpm for 30 min, and repeated 3 times.

[0066] 2) The precipitate after centrifugation is placed in a crucible and reacted in a muffle furnace at 600° C. for 1 h to obtain in-situ grown nano-calcium oxide.

[0067] 3) Preparation of silane-modified polycarboxylic acid dispersant: aminoethylaminoisobutylmethyldimethoxysilane, polycarboxylic acid dispersant and deionized water were mixed in a ratio of 4:6:90 and added into a reactor, stirred at a speed of 100 r / min for 1 h, and 32% NaOH solution was added to adjust the pH to 12 to obtain a silane-modified polycarboxylic acid dispersant.

[0068] 4) Preparation of calcium silicate nanocrystalline cores: 5.1 g of in-situ grown nano calcium oxide and 213 g of silane-modified polycarboxylic acid dispersant were added to a reactor and mixed and stirred for 20 min. 15 g of sodium silicate nonahydrate was prepared into a 10% solution and added dropwise to the reactor while stirring for 30 min. After the addition was completed, stirring was continued for 1 h to obtain calcium silicate nanocrystalline cores.

[0069] Comparative Example 2

[0070] A method for preparing a calcium silicate crystal nucleus early strength agent comprises:

[0071] 1) Preparation of in-situ growth calcium source: 1.5 g pretreated graphite, 3.0 g calcium nitrate, 0.5 g lactic acid, and 55 g water were mixed in a 250 mL conical flask, stirred at 25°C for 10 min, and 6 g 1 mol / L NaOH solution was added dropwise to the stirred conical flask using a peristaltic pump for 30 min. The product in the conical flask was poured into a centrifuge tube and centrifuged at 16,000 speed for 30 min, and repeated 3 times.

[0072] 2) The precipitate after centrifugation is placed in a crucible and reacted in a muffle furnace at 600° C. for 1 h to obtain in-situ grown nano-calcium oxide.

[0073] 3) Preparation of modified polycarboxylic acid dispersant: polycarboxylic acid dispersant and deionized water were mixed in a ratio of 6:94 and added into a reactor, stirred at a speed of 100 r / min for 1 h, and 32% NaOH solution was added to adjust the pH to 12 to obtain polycarboxylic acid dispersant.

[0074] 4) Preparation of calcium silicate nanocrystalline cores: 5.1 g of in-situ grown nano calcium oxide and 213 g of silane-modified polycarboxylic acid dispersant were added to a reactor and mixed and stirred for 20 min. 28 g of sodium silicate nonahydrate was prepared into a 10% solution and added dropwise to the reactor while stirring for 30 min. After the addition was completed, stirring was continued for 1 h to obtain calcium silicate nanocrystalline cores.

[0075] Comparative Example 3

[0076] In this comparative example, the pretreated graphite was omitted, and the other conditions were the same as those in Example 4.

[0077] Comparative Example 4

[0078] In this comparative example, the aminoethylaminoisobutylmethyldimethoxysilane in step 3) is omitted, and the remaining conditions are the same as those in Example 4.

[0079] Comparative Example 5

[0080] The preparation method of the calcium silicate crystal nucleus early strength agent of this comparative example is as follows: weigh 15.0g of polycarboxylic acid water reducer and 140.0g of water, add them to the reactor and start stirring, and set the stirring rate to 300rpm. Weigh 10.4g of calcium nitrate tetrahydrate and 22.6g of water, mix and configure into a calcium nitrate aqueous solution; weigh 8.5g of sodium metasilicate pentahydrate and 23.5g of water to configure into a silicate aqueous solution with an effective concentration of 15wt%, and finally weigh 1.5g of a sodium hydroxide aqueous solution with a concentration of 55.0wt%. The above-mentioned mixed aqueous solution, silicate aqueous solution and sodium hydroxide aqueous solution are dripped into the reactor, and the dripping rate is controlled so that the dripping time is 2.5h. After dripping, continue stirring for 24h to obtain the calcium silicate crystal nucleus early strength agent.

[0081] Comparative Example 6

[0082] This comparative example prepared an early strength agent according to Example 1 of CN112830710A.

[0083] Comparative Example 7

[0084] In this comparative example, steps 1)-2) are omitted, and the in-situ grown nano calcium oxide in step 4) is directly replaced with an equal amount of commercially available nano calcium oxide (particle size 40-50 nm), and the other conditions are the same as those in Example 4.

[0085] Comparative Example 8

[0086] In this comparative example, the pretreated graphite is replaced with graphite powder (particle size 1-20 μm) of equal mass, and the other conditions are the same as those in Example 4.

[0087] The particle size of the crystal core early strength agent prepared in the embodiment and the comparative example was tested by a nano-particle size analyzer, and the stability of the calcium silicate nano-crystal core was tested by visual observation at room temperature. The results are shown in Table 1.

[0088] Table 1

[0089]

[0090]

[0091] It can be seen from the data in Table 1 that the particle size of the crystal nucleus early strength agent synthesized by the scheme of the present invention is mainly distributed in 90-140nm, and the particle size is much smaller than that of the comparative example, indicating that this scheme can effectively control the particle size of the crystal nucleus early strength agent. In addition, the early strength agent prepared by the present invention has good stability, because the in-situ growth technology is more conducive to the regulation of the crystal nucleus particle size and the dispersion of the crystal nucleus, and the silane-modified polycarboxylic acid water-reducing agent is more conducive to improving stability.

[0092] Whether the preparation method of the in-situ grown calcium source is changed or the preparation method of the silane-modified polycarboxylic acid dispersant is changed, or the early strength agent prepared by the prior art is used, its stability is far worse than that of the early strength agent prepared in the embodiment of the present invention; the graphite powder is not treated and cannot be evenly dispersed, and has poor stability.

[0093] The early strength agents prepared in the embodiment and the comparative example were mixed with concrete respectively. The early strength agent addition amount was 4% of the mass of the concrete. The concrete formula was shown in Table 2. The compressive strength of the concrete was tested in accordance with GB50081-2019, and the results were shown in Table 3.

[0094] Table 2

[0095]

[0096] Table 3

[0097]

[0098]

[0099] As shown in Table 3, the concrete added with the crystal nucleus early strength agent has improved strength at 8h, 12h, 24h and 28h compared with the blank sample, especially the early strength. The early strength of the concrete in Example 4 is 3.6Mpa at 8h, and the time taken to reach the same strength is 4h earlier than that of the blank concrete. This is fully expected to directly replace the high temperature steam curing process and solve the problems of high energy consumption and high pollution in the production process of prefabricated components.

[0100] In summary, the present invention utilizes the high dispersibility of the growth carrier in water to grow nano calcium oxide on the carrier, thereby improving the dispersibility of nano calcium oxide in water, and utilizes aminosilane to modify the polycarboxylic acid dispersant so that the nano CSH crystal nucleus dispersant has high dispersibility and high stability, thereby achieving the best-selling and stable dispersion of the early strength agent.

[0101] The above is a preferred embodiment of the present invention. For ordinary technicians in this technical field, making several improvements and modifications without departing from the principles of the present invention should also be regarded as within the protection scope of the present invention.

Claims

1. A method for preparing a nanocrystalline core-type early strength agent using in-situ growth technology, characterized in that: include: 1) stirring and mixing the pretreated graphite, calcium source and carboxylate evenly, adding sodium hydroxide dropwise to the mixture at a uniform speed at 20-50° C., and then washing by centrifugation with deionized water to obtain in-situ grown nano calcium hydroxide; 2) calcining nano calcium hydroxide at 500-700° C. to obtain nano calcium oxide; 3) stirring and mixing the polycarboxylic acid dispersant, the silane modifier and deionized water, and adjusting the pH to 11-13 by adding sodium hydroxide solution to obtain a silane-modified polycarboxylic acid dispersant; 4) The silane-modified polycarboxylic acid dispersant of step 3) and the nano calcium oxide of step 2) are uniformly mixed, and then a silicon source of a certain concentration is uniformly added dropwise to the mixture to obtain a CSH nanocrystalline core dispersant.

2. The method according to claim 1, characterized in that In the step 1), the graphite is pretreated by mixing graphite and concentrated sulfuric acid in a mass ratio of 1:1, grinding with a grinder for 30 minutes, then removing excess sulfuric acid by centrifugal washing, and drying for later use.

3. The method according to claim 2, characterized in that In the step 1), the mass ratio of the pretreated growth carrier, calcium source and carboxylate is 1-2.5:4-12:1 In the step 3), the mass ratio of the polycarboxylic acid dispersant, the silane modifier, and the deionized water is 6:1-3:88-93; In the step 4), the mass ratio of the polycarboxylic acid dispersant to the nano calcium oxide is 3-11:100; The molar ratio of the silicon source to the calcium source is 1:0.7-1.

5.

4. The method according to claim 3, characterized in that The calcium source is one or more of calcium chloride, calcium nitrate, calcium sulfate, calcium gluconate, and calcium lactate; The carboxylate is one or more of sodium citrate, sodium tartrate, sodium gluconate, sodium acetate, sodium oxalate, sodium lactate, sodium stearate, and sodium acrylate.

5. The method according to claim 4, characterized in that In the step 3), the silane modifier is one or more of aminosilane, 3-aminopropyltriethoxysilane, bis(tert-butylamino)silane, (3-aminopropyl)dimethylmethoxysilane, 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane, [3-(6-aminohexylamino)propyl]trimethoxysilane, and aminoethylaminoisobutylmethyldimethoxysilane.

6. The method according to claim 5, characterized in that In the step 4), the silicon source is sodium silicate nonahydrate and / or sodium silicate tetrahydrate.

7. A nanocrystalline core-type early strengthening agent prepared by the method described in any one of claims 1 to 6.

8. The use of the nanocrystalline core-type early strength agent according to claim 7, characterized in that: Added to concrete as an early strength agent, the addition amount is 4-10% of the concrete mass.

Citation Information

Patent Citations

  • Coupling agent modified nano hydrated calcium silicate crystal nucleus early strength agent and preparation method thereof

    CN112830710A

Cited By

  • Preparation method and application of silane composite nano C-S-H for hydrophobic modification of concrete surface

    CN122102739A